2013
DOI: 10.1093/ije/dyt183
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal paracetamol exposure and child neurodevelopment: a sibling-controlled cohort study

Abstract: Children exposed to long-term use of paracetamol during pregnancy had substantially adverse developmental outcomes at 3 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
260
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(285 citation statements)
references
References 29 publications
17
260
2
6
Order By: Relevance
“…Mean scores were calculated and standardized. Previous studies reported adequate reliability for the externalizing and internalizing behavior scales (30). The subset of items used in MoBa has been found to be representative (34).…”
Section: Neurodevelopmental Outcomesmentioning
confidence: 85%
See 1 more Smart Citation
“…Mean scores were calculated and standardized. Previous studies reported adequate reliability for the externalizing and internalizing behavior scales (30). The subset of items used in MoBa has been found to be representative (34).…”
Section: Neurodevelopmental Outcomesmentioning
confidence: 85%
“…Mean scores were calculated and standardized. Good reliability of the scale in MoBa was previously demonstrated with the use of a 2-parameter item response theory analysis (mean factor loading: 0.82) (30).…”
Section: Neurodevelopmental Outcomesmentioning
confidence: 90%
“…In our most recent study published we found that three year old children who had been exposed to paracetamol (=acetaminophen) for more than 28 days during fetal life had poorer gross motor development, communications skills and more externalizing problems compared to their unexposed siblings (21). The effect size was approximately one quarter of a standard deviation (e.g.…”
Section: Medication Safety On Neurodevelopmental Outcomesmentioning
confidence: 92%
“…We have also performed exome sequencing for a smaller number of trios with the aims of detecting de novo mutations and the presence of rare disease-promoting alleles and chromosomal changes associated with autism spectrum disorders. The discordant co-sibling design is increasingly used among the large number of sibships in MoBa, one example being the finding that prolonged intake of paracetamol in pregnancy was associated with adverse child developmental outcomes at three years (27).…”
Section: Presentmentioning
confidence: 99%